Soutenir le développement professionnel des enseignants en haute école par la recherche : analyse d’un dispositif d’appel à projets interne - Sandrine Biémar; Birgit Quinting; Isabelle Bragard (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
The 2013 decree defining the missions of higher education institutions in the Wallonia-Brussels Federation of Belgium identified applied research as a full-fledged mission of the university college. However, the professional project of teachers who evolve in university college is initially guided by teaching. In order to align its teaching staff with this new mission, one university of applied sciences has set up a call for internal projects. The study presented in this article takes as its object the novel professional development of teachers involved in research projects. With a view to the continuous improvement of the call process, its comprehensive and exploratory aim is to document the process of identity construction in which these teacher-researchers are involved, to identify the learning achieved as well as the facilitators and obstacles perceived. Finally, 51 teachers were interviewed by means of an individual online questionnaire. The data were analysed with a qualitative method. The results indicate, among other things, that the desire to do research is linked to the desire to improve and inform one's teaching practices. In this respect, the Scholaship of Teaching and learning approach (Brew, 2010) could shed light on the specificity of the professional development process in HE. The main obstacle remains the time allocated to the research project, which is both too short and difficult to combine with the time allocated to teaching. Levers are identified in the collective dynamics within and between project teams as well as in the institutional support that is necessary.